2007
DOI: 10.1007/s11250-007-9090-5
|View full text |Cite
|
Sign up to set email alerts
|

Bovine mastitis and antibiotic resistance patterns in Selalle smallholder dairy farms, central Ethiopia

Abstract: A study was conducted to determine the prevalence of mastitis, identify the major bacterial pathogens and test the antimicrobial resistance of milk bacterial isolates in smallholder dairy farms in Selalle area, Ethiopia. A total of 109 smallholder dairy farms comprising 500 crossbred lactating cows were included. The prevalence of clinical mastitis at herd, cow and quarter level was 8.3% (n=9), 1.8% (n=9) and 0.51% (n=10), respectively, while that of sub-clinical mastitis was 54.7%, 22.3% and 10.1%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
54
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 11 publications
24
54
9
Order By: Relevance
“…The study indicated that staphylococci was isolated most were from camels ' milk. This is in agreement with the findings by Kivaria et al (2007), Getahun et al (2008), Olde et al (2008) and Alzohairy (2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The study indicated that staphylococci was isolated most were from camels ' milk. This is in agreement with the findings by Kivaria et al (2007), Getahun et al (2008), Olde et al (2008) and Alzohairy (2011).…”
Section: Discussionsupporting
confidence: 94%
“…Pseudomonas species was higher than Grampositive bacterial genera, Staphylococcus and Corynebacterium; are known to be part of the normal microfolra and some can cause disease such as mastsides in cattle (Getahun et al, 2008;Holmes and Zadoks, 2011). These results are in agreement with other studies which indicated that the commonly isolated genera were Staphylococcus, Escherichia and Salmonella (Van Duijkeren et al, 2004;Alzohairy, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The major streptococcal strains isolated from this study was S. uberis found to be highest followed by S. agalactiae. Results are in agreement with previous studies [7,8,18]. The predominance of microbes varies with mastitic cases, geographical areas, breeds and climatic conditions as reported previously [8-10, 18, 20].…”
Section: Discussionsupporting
confidence: 93%
“…Prevalence of subclinical mastitis (33.85%) is higher than that of clinical mastitis (9.64%) in the present study, which is agreement with several earlier reports from different parts of Ethiopia [25][26][27][28][29][30] since, environmental factors play significant role, the prevalence of subclinical mastitis varies in different dairy farms [31].…”
Section: Conclusion and Recommendationssupporting
confidence: 92%